Soft Skills and Creative Activity: Analysis of Interconnection in the Education of Future Graphic Design Professionals - Vitchynkina, Kateryna (Educational Challenges, 2024)
The purpose is to conduct a comprehensive analysis of the correlation between soft skills and indicators of creative activity among future graphic design professionals, utilizing methods of theoretical analysis of educational standards. The relevance of this research is determined by the necessity to develop soft skills and creative activity in future professionals in graphic design within the framework of the contemporary job market. Methodology. Theoretical methods involve a review of scientific literature to understand existing perspectives and research on soft skills and creative activity, aiming to elucidate key concepts and theories. Analysis and synthesis are employed to scrutinize educational programs, standards of People’s Republic of China (PRC) and the United Kingdom (UK), and industry-specific criteria in graphic design, identifying key elements related to soft skills and creative activity. Results. The study characterizes and clarifies that educational standards recognize the importance of cultivating “soft skills” in future graphic design professionals. It highlights the interaction and complementarity of soft skills and personality traits, which define specific knowledge and abilities and reflect distinctive characteristics and values. The research compares soft skills (communication, creativity, problem-solving, critical thinking, and time management) with specific personality traits (interest, originality, independence, initiative, and energy) in the context of their interrelation in the field of graphic design. Conclusions. Soft skills and indicators of creative activity are interconnected and mutually reinforce each other in the process of graphic design projects. Soft skills provide the foundation for the effective utilization of indicators of creative activity. It is pointed out that further research is needed to determine the levels of development of creative activity among future professionals in graphic design concerning the identified indicators.